2022
DOI: 10.1021/acsanm.2c03346
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Functionalization and Crystallinity in Nanoporous Organic Frameworks for Effective Removal of Metal Ions from Aqueous Solution

Abstract: In order to search effective adsorbents for removal of metal ions in water treatments, three nanoporous organic frameworks, TPPA, TPPA-SO 3 H, and TPBD-SO 3 H, with or without −SO 3 H functionalities were selected and synthesized by the Schiff base reactions of 1,3,5-triformylphloroglucinol (TP) and p-phenylenediamine (PA), p-phenylenediaminesulfonic acid (PA-SO 3 H), and 2,2′-benzidinedisulfonic acid (BD-SO 3 H), respectively. Characterizations revealed that both TPPA and TPPA-SO 3 H possess high crystallinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Recently, a class of organic polymeric porous materials with crystalline and periodic structures, that is, covalent organic frameworks (COFs), have shown highly promising potential in the applications of heterogeneous catalysis, chemical sensing, bio-imaging, , and photodynamic therapy, proton conduction, and energy storage, as well as adsorption and separation to kinds of ions and molecules, including iodine. Due to their inherent porosity and strong covalent bonding of the organic components with light elements such as C, H, O, and N, COF materials not only show low density and relatively high stability but also display chemical tenability. For instance, functional organic moieties with photoresponsive activity, proton-transport properties, and even chiral centers have been introduced into the COFs during the syntheses of precursors or post-modification of the constructed frameworks for photocatalysis, proton conduction, , and asymmetric catalysis, respectively. Previous works on iodine adsorption revealed that by decorating the framework with nitrogen-rich groups, the adsorption capacity of iodine can be significantly improved. Thus, introducing nitrogen-rich groups into the COFs should be a feasible way for the fabrication of effective iodine adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a class of organic polymeric porous materials with crystalline and periodic structures, that is, covalent organic frameworks (COFs), have shown highly promising potential in the applications of heterogeneous catalysis, chemical sensing, bio-imaging, , and photodynamic therapy, proton conduction, and energy storage, as well as adsorption and separation to kinds of ions and molecules, including iodine. Due to their inherent porosity and strong covalent bonding of the organic components with light elements such as C, H, O, and N, COF materials not only show low density and relatively high stability but also display chemical tenability. For instance, functional organic moieties with photoresponsive activity, proton-transport properties, and even chiral centers have been introduced into the COFs during the syntheses of precursors or post-modification of the constructed frameworks for photocatalysis, proton conduction, , and asymmetric catalysis, respectively. Previous works on iodine adsorption revealed that by decorating the framework with nitrogen-rich groups, the adsorption capacity of iodine can be significantly improved. Thus, introducing nitrogen-rich groups into the COFs should be a feasible way for the fabrication of effective iodine adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of another species with a similar charge had a minor to moderate interfering effect on the targeted metal analytes, causing lower maximum extraction capacities for selected metals, which resulted in the different trend Bi 3+ ≥ Pb 2+ > Ag + > Cd 2+ ≥ As 3+ > Co 2+ regarding the elution efficiency. The observed phenomenon presumably has two possible reasons: (1) high oxidation state of the central metal ion and (2) metal electronegativity (EN) . The EN plays an important role in the case of nonpure electrostatic extraction along with the oxidation state.…”
Section: Resultsmentioning
confidence: 99%
“…The observed phenomenon presumably has two possible reasons: (1) high oxidation state of the central metal ion and (2) metal electronegativity (EN). 32 The EN plays an important role in the case of nonpure electrostatic extraction along with the oxidation state. The EN of Pb 2+ is 2.33, compared to the EN of Bi 3+ of 2.02, however because Bi 3+ has a higher oxidation state, an almost equal extraction efficiency was seen.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Their distinct structural features, including a large surface area, adjustable pore dimensions, and outstanding stability, render them particularly suitable for use in water purification applications [ [20] , [21] , [22] , [23] ]. Different molecules can be added or changed to tailor and enhance COFs at the level of atoms, which enables exact manipulation of their physical and chemical attributes to boost the effectiveness of pollutant extraction and the treatment of wastewater [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. Within the field of separation science, the utilization of COFs has largely been dependent on their π–π stacking interactions and innate hydrophobic traits.…”
Section: Introductionmentioning
confidence: 99%